E-Wallet Preferences and Impact on Islamic Banking Innovation Among University Students - Habibah Ramadhani Nasution; Zuhrinal M Nawawi; Atika Atika (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The rapid development of digital payment technology has increased the use of e-wallets among various groups, including Islamic economics students. This study aims to examine the effects of attitude, subjective norm, and perceived behavioral control on e-wallet payment preferences among students of the Faculty of Islamic Economics and Business (FEBI), UIN Sumatera Utara, using the Theory of Planned Behavior (TPB). A quantitative approach was employed, involving 97 respondents selected through purposive sampling. The data were analyzed using multiple linear regression. The results indicate that attitude has a positive and significant effect on e-wallet preferences, while subjective norm and perceived behavioral control do not have significant effects. The model explains 35.6% of the variance in e-wallet preferences. These findings suggest that students’ digital payment preferences are influenced more by their personal evaluations of e-wallet usage than by social influences or perceived control. This study contributes to the TPB literature in the context of Islamic economics students by highlighting the dominant role of attitude in shaping e-wallet preferences. Practically, the findings provide insights for Islamic banks in developing digital services that are more aligned with users’ needs and expectations.